The Influence of Problem Based Learning Model Based on Midwifery First Stage of Childbirth Care Module in Improving Learning Quality - Ahmar, Hamdiah; Budi, Prastawa; Ahmad, Mardiana; Mustary, Musliha; Octaviana Hutagaol, Iin (International Journal of Psychosocial Rehabilitation, 2020)
The emphasis of midwifery education is the process of educating and increasing the ability of individuals to become midwives who are carrying out professional midwifery practice. Several factors cause the low quality of education. One of them is the learning process; another one is the lack of learning media and the selection of inappropriate learning methods. The aim of this study was to analyze the effects of PBL based on the midwifery 1st stage of the child care module on improving learning quality. This research is a quasi-experiment with one group pretest and post-test design, carried out at the Palagonia Academy of D3 study program in Makassar in December 2019. Harry King nomograme large sample formula is used with 114 samples withdrawn with purposive sampling technique. The instruments of the study were module preparation instruments in the form of validation sheets from student activity observation sheets, partograph problems, and student response questionnaires. Data were analyzed with the Wilcoxon test, the N-Gain test, and the Fisher test. Module research results are categorized as very feasible to use, student learning activities are very good with an average of 89.96%, learning outcomes indicate an influence of module-based PBL (Wilcoxon Test) p-value 0.000 0.05, and student responses are 76 with an interesting category.